Dialectics and rhetoric: Socrates and Gorgias - Disselkoen, Hugo Renato Ochoa (2015)
The aim here is to use a comparison between the discourse of Socrates in the Apology and that of Gorgias in his Encomium of Helen in order to set out the reach and limits of a discourse that aims to be purely rational, that is, of a discourse that refuses to use elements of rhetoric. Also, since the Encomium is in fact a eulogy of rhetoric, the meaning of this defense and its foundation are analyzed.